Extending the kantorovich theory for solving equations - Argyros, Ioannis K; Magreñán, Á. Alberto (Iterative Methods and Their Dynamics with Applications: A Contemporary Study, 2020)
Let X, Y be Banach spaces, D ⊂ X be convex, F : D ⊂ X → Y be a Fréchet differentiable operator. We shall determine a solution x of the equation F(x) = 0, Many problems from Applied Sciences can be solved finding the solutions of equations in a form like (6.1) [5, 9, 12, 13, 27, 31-33].
Capítulo del libro "Iterative Methods and Their Dynamics with Applications"
Keywords: computer science; mathematics & statistics; Scopus(2); WOS(2)